Prolonged Deleterious Influences of Chemotherapeutic Agent CPT-11 on Resident Peritoneal Macrophages and B1 Cells - Bai, Wen-Jing; Li, Chen-Guang; Zhang, Cheng-Cheng; Xu, Li-Hui; Zeng, Qiong-Zhen; Hu, Bo; Hong, Zhou; He, Xian-Hui; Ouyang, Dong-Yun (Frontiers in Immunology, 2018)
CPT-11 is a first-line chemotherapeutic agent for the treatment of colorectal cancer in clinic. Previous studies including ours have demonstrated that CPT-11 is however toxic to the intestinal epithelium and resident peritoneal macrophages. By interacting with B1 cells, the resident peritoneal macrophages play critical roles in the maintenance of gastrointestinal homeostasis. It remains therefore elusive whether these peritoneal innate immune cells could be rebuilt spontaneously or artificially after being impaired by CPT-11 administration. In this study, we found that mouse resident peritoneal macrophages, namely the large peritoneal macrophages (LPMs) with a CD11b+F4/80hiGATA6+ phenotype, and B1 (CD19+CD23−) cells were depleted by intraperitoneal CPT-11 treatment within one week, but reappeared from day 14 after CPT-11 treatment. However, the recovery processes of these innate immune cells were slow, as their counts could not be fully recovered even 2 months later, as compared to that of vehicle-treated control group. Interestingly, in the peritoneal cavity of the mice treated with CPT-11, the cell counts of LPMs and B1 cells were significantly increased after adoptive transfer with syngeneic peritoneal exudate cells from healthy mice. Adoptive transfer with bone marrow cells also slightly increased, although not significantly, the cell counts of LPMs and B1 cells in CPT-11-treated mice. The survival rate of bacterial infected mice was significantly reduced by intraperitoneal CPT-11 treatment in comparison to vehicle-treated or untreated control groups. Besides, oral administration of CPT-11 also had a delayed toxicity on the resident peritoneal macrophages. Our results suggest that CPT-11 has prolonged deleterious effects on peritoneal innate immune cells but adoptive transfer with peritoneal exudate cells may accelerate their recovery processes, highlighting the potential of adoptive cell transfer as an avenue to counteract the adverse effects of this chemotherapeutic agent.